Fear of (re)injury and return to work following compensable injury: qualitative insights from key stakeholders in Victoria, Australia - Samantha Bunzli; Nabita Singh; Danielle Mazza; Alex Collie; Agnieszka Kosny; Rasa Ruseckaite; Bianca Brijnath (BMC, 2017)
Abstract Background Return to work (RTW) is important for recovery post-injury. Fear of (re)injury is a strong predictor of delayed RTW, and therefore much attention has been given to addressing injured workers' fear beliefs. However, RTW is a socially-negotiated process and it may be important to consider the wider social context of the injured worker, including the beliefs of the key people involved in their RTW journey. Methods This paper involves data collected as part of a wider study in which semi-structured interviews explored RTW from the perspectives of 93 key stakeholders: injured workers, GPs, employers and insurance case managers in Victoria, Australia. Inductive analysis of interview transcripts identified fear of (re)injury as a salient theme across all stakeholder groups. This presented an opportunity to analyse how the wider social context of the injured worker may influence fear and avoidance behaviour. Two co-authors performed inductive analysis of the theme 'fear of (re)injury'. Codes identified in the data were grouped into five categories. Between and within category analysis revealed three themes describing the contextual factors that may influence fear avoidance and RTW behaviour. Results Theme one described how injured workers engaged in a process of weighing up the risk of (re)injury in the workplace against the perceived benefits of RTW. Theme two described how workplace factors could influence an injured workers' perception of the risk of (re)injury in the workplace, including confidence that the source of the injury had been addressed, the availability and suitability of alternative duties. Theme three described other stakeholders' reluctance to accept injured workers back at work because of the fear that they might reinjure themselves. Conclusions Our findings illustrate the need for a contextualised perspective of fear avoidance and RTW behaviour that includes the beliefs of other important people surrounding the injured worker (e.g. employers, family members, GPs). Existing models of health behaviour such as The Health Beliefs Model may provide useful frameworks for interventions targeting the affective, cognitive, social, organisational and policy factors that can influence fear avoidance or facilitate RTW following injury.